RESPON PERTUMBUHAN SERTA ANATOMI DAUN KENARI (Canarium commune L) DAN AKASIA (Acacia mangium Willd) TERHADAP EMISI GAS KENDARAAN BERMOTOR - Siti Badriyah Rushayati; Rizky Yusuf Maulana (Media Konservasi, 2005)
Canarium and Acacia plants are commonly used as urban forest and shade plants on the right-left side of streets. Identifying the effect of air pollution to the growth and microscopic anatomy of the leaves will be beneficial in predicting air quality condition of the location. Result of the research showed that canarium plants exposed to air pollutant emission showed a lower diameter growth and higher stoma density compare to the ones unexposed to pollutant. Acacia plants exposed to air pollutant emission showed smaller amount of diameter growth, height growth, length of upper side stomata, length of lower side stomata, leaves thickness, lower side palisade tissue thickness and sponge tissue thickness compare to the plants unexposed to pollutant. Acacia plant was more sensitive to air pollutant because more tissues experienced disturbance and destruction. Acacia plant might be a bioindicator of air pollution.Keywords : urban forest, air pollution, growth, microscopic anatomy of the leaves, bioindicator